2023
DOI: 10.1088/1748-9326/acf603
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential benefits of methane oxidation technologies using a concentration-based framework

Sam Abernethy,
Max I Kessler,
Robert B Jackson

Abstract: Lowering the atmospheric methane concentration is critical to reducing short-term global warming because of methane’s high radiative forcing and relatively short lifetime. Methane could be destroyed at its emissions sources or removed from the atmosphere by oxidizing it to carbon dioxide and water vapor, greatly lowering the warming effect. Here we provide, to the best of our knowledge, the first estimate of the amount of methane that is emitted at a given concentration. We use this to assess the potential ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Abernathy et al [17] found that light-based reactors must have a quantum yield for methane removal of at least 9 ± 8%, in order for the economic benefit of removing methane to exceed the energy cost. Given the demonstrated performance of MEPS with an AQY of 0.83% and anticipated improvements, the possibility that MEPS will meet the target set by Abernathy et al cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abernathy et al [17] found that light-based reactors must have a quantum yield for methane removal of at least 9 ± 8%, in order for the economic benefit of removing methane to exceed the energy cost. Given the demonstrated performance of MEPS with an AQY of 0.83% and anticipated improvements, the possibility that MEPS will meet the target set by Abernathy et al cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper by Abernethy et al [17] has assessed methane oxidation technologies using a concentration based framework. This paper estimates, for the first time, the amount of methane emitted at a given concentration, showing that around 3/4 of methane emissions occur at a concentration below 1000 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…the chemical or biological conversion to carbon dioxide and water). Because methane is 43 times more potent than carbon dioxide per molecule, this conversion substantially reduces warming [15]. Roughly 95% of the methane sink is due to highly reactive atmospheric radicals (mainly hydroxyl, with a minor contribution from chlorine), while ∼5% is due to soil methanotrophs (methaneconsuming microbes) [5].…”
Section: Methane Removal Approaches and Proposed Evaluation Criteriamentioning
confidence: 99%
“…To be cost-effective at atmospheric concentrations, however, substantial breakthroughs are needed. For heat-based reactors, the operating temperature likely must be reduced from the current low of 300 • C down to below 30 • C [15]. For light-based reactors, including those that use photocatalysts and photolysis-based radical generation, the quantum efficiency (the ratio of oxidized methane molecules to incident photons) will need to be increased-from the current high of 0.8% potentially to at least 9% [15,19].…”
Section: Methane Removal Approaches and Proposed Evaluation Criteriamentioning
confidence: 99%
See 1 more Smart Citation